Asset price booms and monetary policy - Carsten Detken; Frank Smets (European Central Bank (ECB), 2004)
The paper aims at deriving some stylised facts for financial, real, and monetary policy developments during asset price booms by means of aggregating information contained in 38 boom periods since the 1970s for 18 OECD countries. We observe 26 macroeconomic variables in a pre-boom, boom and post-boom phase. Not all booms lead to large output losses. We divide our sample in high-cost and low-cost booms and analyse the differences. High-cost booms are clearly those in which real estate prices and investment crash in the post-boom periods. In general it is difficult to distinguish a highcost from a low-cost boom at an early stage. However, high-cost booms seem to follow very rapid growth in the real money and real credit stocks just before the boom and at the early stages of a boom. During high-cost booms, rates of change of real estate prices and consumption growth are significantly higher and the investment (especially housing) GDP ratio deviation from trend rises faster over the whole boom period. There is also evidence that high-cost booms are associated with significantly looser monetary policy conditions over the boom period, especially towards the late stage of a boom. We finally discuss the results with regard to the theoretical literature. The looser monetary policy at the later stage of high-cost booms could be interpreted in different ways. It could be that excessively loose monetary policy contributes to extending the boom and exacerbating the real and financial imbalances. Alternatively, observed monetary policy could reflect a desirable, pre-emptive loosening in anticipation of an asset price crash to come.
Keywords: E44; E52; E58; 330; and monetary policy developments; real; The paper aims at deriving some stylised facts for financial